Distinct Patterns and Aetiology of Chromonychia - Soo Hyeon Bae; Min Young Lee; Jee-Bum Lee (Medical Journals Sweden, 2017)
Abnormal colouring of the nails may be a sign of underlying systemic or local disorders. This study investigated the prevalence and causes of chromonychia as a whole, as well as of each subtype. Among 163 patients with chromonychia, trauma was the pathogenesis in up to 20.9% (34/163) of cases. The most common subtype was melanonychia (54.0%; 88/163), followed by leukonychia (23.9%), red (8.6%), green (6.7%), yellow (4.9%) and blue (1.8%) nails. Nail matrix naevus (33.3%; 29/88) was the most common cause of melanonychia, while skin diseases (41.0%; 16/39), such as psoriasis (75%, 12/16) and alopecia areata (18.8%; 3/16), in addition to systemic diseases (33.3%; 13/39) including anaemia (38.5%, 5/13) and chronic renal failure (15.4%; 2/13) were the dominant causes of leukonychia. As chromonychia may be the first or only sign of an underlying disorder, it should alert physicians and patients to the need for a prompt and thorough evaluation.